Extending High Fatty Foods Shelf-Life Protecting from Lipid Oxidation and Microbiological Contamination - Andrade, Mariana A. (2023)
This paper was carried out under the MobFOOD Project (POCI-01-0247-FEDER-024524 and LISBOA-01-0247-FEDER-024524), funded by POCI (Operational Programme “Competitiveness and Internationalization”) and POR Lisboa (Lisbon Regional Operational Programme), through ANI, and by the Programa de Cooperación Interreg-A España–Portugal (POCTEP) 2014–2020 (project 0377_IBERPHENOL_6_E). . Funding Information: Cássia H. Barbosa is grateful for her Ph.D. Grant 2021.08154.BD is funded by Foundation for Science and Technology (FCT), Portugal. The authors also would like to thank Talho Girassol, LDA, for kindly supplying the beef meat samples and Sidney Tomé for his contribution to the statistical analysis. Publisher Copyright: © 2023 by the authors.